Criminal Responsibility for Prison Officers Who Carry Out Extortions (Pungli) in the KPK Detention Center Area - Andhijaya, Moch Ramadhan Dewa; Simangunsong, Frans (Activa Yuris: Jurnal Hukum, 2025)
Extortion by prison officers is unacceptable behavior and a form of corruption. It can have serious consequences, not only for public confidence in the legal system and custody, but also for the welfare and rights of individuals under the supervision of the prison. Extortion can occur in various forms, from withdrawing funds in exchange for special treatment to prisoners, selling prohibited goods in prison, to extorting prisoners or their families to obtain complete facilities that should not be available or accessible to prisoners. Extortion in the KPK prison refers to corrupt practices within the institution, which should be a place where law enforcement against corruption is prioritized. The KPK (Corruption Eradication Commission) is an Indonesian government agency established to combat corruption. If there are reports or allegations of extortion in the KPK prison, it is very serious and must be investigated thoroughly. Corruption within law enforcement agencies, especially those tasked with combating corruption such as the KPK, is a betrayal of public trust and undermines the integrity of the justice system. Therefore, if there are indications of extortion in the KPK detention center, firm and transparent law enforcement measures must be taken to uphold justice and ensure that the institution remains at the forefront of fighting corruption.